2014
DOI: 10.1074/jbc.m114.575779
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin-related Protein 1 (Drp1) Promotes Structural Intermediates of Membrane Division

Abstract: Background: Drp1 mediates mitochondrial division via a poorly understood mechanism. Results: Drp1 promotes giant vesicle tethering and concentrates at contact sites in structures similar to those found in dividing mitochondria. Conclusion: Besides membrane constriction, Drp1 stabilizes structural intermediates of membrane division. Significance: This new role of Drp1 helps us understand mitochondrial biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
62
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 76 publications
11
62
1
Order By: Relevance
“…In fact, the accompanying article (42) clearly shows that Mff stimulation of Drp1 activity is synergistic with CL stimulation. These results are congruent with previous reports of VD interactions with CL that promote Drp1 recruitment to lipid bilayers (21,(23)(24)(25). Given that CL has been shown to stabilize dimeric Drp1 at the lipid surface to promote Drp1 self-assembly (23), we propose that CL interactions at the membrane directly promote Drp1 dimer interactions with Mff (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In fact, the accompanying article (42) clearly shows that Mff stimulation of Drp1 activity is synergistic with CL stimulation. These results are congruent with previous reports of VD interactions with CL that promote Drp1 recruitment to lipid bilayers (21,(23)(24)(25). Given that CL has been shown to stabilize dimeric Drp1 at the lipid surface to promote Drp1 self-assembly (23), we propose that CL interactions at the membrane directly promote Drp1 dimer interactions with Mff (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Initially, the role of the VD was examined based on its apparent proximity to the membrane as well as its ability to interact with CL (21,23,25). This proposed location would also place it directly adjacent to receptor proteins on the OMM to promote intermolecular interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VD has been proposed to interact directly with negatively charged lipid (20,21). Nevertheless, the ⌬VD mutant was found to assemble on both negatively charged liposomes used in these studies.…”
Section: Discussionmentioning
confidence: 65%
“…The middle and GED domains promote self-assembly through oligomerization interaction interfaces (19). The role of the VD is currently debated, but recent studies have identified a role in lipid interactions (20,21). Collectively, these domains work in concert to promote cycles of protein assembly and disassembly at sites of membrane remodeling.…”
mentioning
confidence: 99%